Is lightning a possible source of the radio emission on HAT-P-11b?. Issue 2 (23rd April 2016) - Hodosán, G.; Rimmer, P. B.; Helling, Ch.
Abstract: Lightning induced radio emission has been observed on Solar system planets. There have been many attempts to observe exoplanets in the radio wavelength, however, no unequivocal detection has been reported. Lecavelier des Etangs et al. carried out radio transit observations of the exoplanet HAT-P-11b, and suggested that a small part of the radio flux can be attributed to the planet. Here, we assume that this signal is real, and study if this radio emission could be caused by lightning with similar energetic properties like in the Solar system. We find that a lightning storm with 3.8 × 10 6 times larger flash densities than the Earth-storms with the largest lightning activity is needed to produce the observed signal from HAT-P-11b. The optical emission of such thunderstorm would be comparable to that of the host star. We show that HCN produced by lightning chemistry is observable 2–3 yr after the storm, which produces signatures in the L (3.0–4.0 μ m) and N (7.5–14.5 μ m) infrared bands. We conclude that it is unlikely that the observed radio signal was produced by lightning, however, future, combined radio and infrared observations may lead to lightning detection on planets outside the Solar system.